Nurses’ Experiences with Work and Family Conflict During the Covid-19 Pandemic: A Qualitative Study - Yuliani Budiyarti; Tresia Eramitha (Department of Nursing, Faculty of Health Sciencce, Universitas Brawijaya, 2022)
The Covid-19 pandemic impacts all aspects of life and all fields of the profession, including nurses, where this can affect physical and psychological health, which impacts the emergence of various new problems, including work and family conflicts. This study aims to explore work and family conflicts experienced by nurses during the Covid-19 pandemic. This study used a qualitative method with a phenomenological approach to get an in-depth picture of the experiences of nurses who experience conflict at work and conflict in the family during the Covid-19 pandemic. Data were collected using in-depth interviews with 12 participants who were taken using the purposive sampling technique. Participants were female and male nurses who work in isolation and non-isolation rooms. Data analysis was carried out thematically inductively through six stages, namely data introduction, code identification, determining the initial theme, reviewing the theme, defining and naming the theme, and the last step is to making a report. The results showed that five themes were identified, namely, (1) role conflict, (2) conflict with family and the surrounding environment, (3) heavy role demands, (4) accepting and undergoing multiple roles, and (5) support in carrying out multiple roles. With the discovery of several new conflicts due to the Covid-19 pandemic, both conflicts at work and conflicts in the family, it is essential for a nurse to adapt to stay balanced in carrying out obligations both as someone professional in their field and as a housewife.